Analyzing Profitability, Firm Size, and Capital Structure’s Impact on Firm Value - Elisa Dwi Handini; Dwi Ermayanti Susilo (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Firm value is a crucial indicator of corporate performance, influenced by profitability, firm size, and capital structure. Understanding these relationships is essential in financial research, particularly in the food and beverage (F&B) sector. Specific Background: Previous studies on Indonesia Stock Exchange (IDX)-listed F&B firms (2021–2023) provide inconsistent findings regarding the effects of profitability and firm size on firm value, with capital structure serving as a potential mediating factor. Knowledge Gap: While some research suggests a direct impact of profitability and firm size on firm value, others argue that these relationships are indirect or insignificant, indicating a need for further investigation. Aims: This study analyzes the influence of profitability and firm size on firm value, considering capital structure as an intervening variable. Methods: A quantitative approach was applied, analyzing data from 17 IDX-listed F&B firms using statistical techniques such as path analysis, classical assumption tests, and hypothesis testing. Results: Profitability and firm size do not significantly affect firm value directly; however, capital structure mediates their influence. Novelty: This study clarifies the mediating role of capital structure in firm value determination, addressing inconsistencies in previous research. Implications: The findings suggest that F&B firms should strategically manage their capital structure to enhance firm value, rather than relying solely on profitability or scale.